There are three laws of indices that need to be remembered to simplify any expression with different indices.

a^m*a^n = a^(m+n)

a^m/a^n = a^(m - n)

(a^m)^n = a^(m*n)

The quadratic formula that gives the roots of a quadratic equation ax^2 + bx + c = 0 is:` x1 =...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

There are three laws of indices that need to be remembered to simplify any expression with different indices.

a^m*a^n = a^(m+n)

a^m/a^n = a^(m - n)

(a^m)^n = a^(m*n)

The quadratic formula that gives the roots of a quadratic equation ax^2 + bx + c = 0 is:` x1 = (-b + sqrt(b^2 - 4ac))/(2a)` and `x2 = (-b - sqrt(b^2 - 4ac))/(2a)`

This is quite a simple formula with the roots differentiated only by the sign before the term `sqrt(b^2 - 4ac)` . Solve a few problems using the formula and you will remember it.